Markovian Approach Enhancement To Simplify Optimal Mean Estimation - Hasan Basari, Abd Samad; Razali, Hazlina; Hussin, Burairah; Asmai, Siti Azirah; Ibrahim, Nuzulha Khilwani; Shibghatullah, Abdul Samad (HIKARI Ltd, 2014)
-